PERLINDUNGAN MEREK BERDASARKAN DAYA PEMBEDA DITINJAU MELALUI DOKTRIN DILUSI (DILUTION DOCTRINE) - Romario Valentino Purba (2023)
The dilution doctrine serves to protect a well-known brand from being used by others in a different product but can undermine its distinctive value and reduce its uniqueness. Differentiation is a very important part of a brand, through differentiating power consumers can identify the origin of goods/services between one producer and another. This journal aims to find out how the protection of brands that have differentiating power through the dilution doctrine is applied in Indonesia and to find out whether the dilution doctrine can only be applied in cases of well-known brands or not. To answer this, the author uses normative juridical research methods where this research uses statutory regulations and uses library materials. The results obtained by the author show that Indonesia does not yet have regulations regarding trademark dilution, but only writes implicitly in Article 21 paragraph 1 of the Law on Trademarks and Geographical Indications (UUMG). Through the cases of IKEA and IKEMA it can be seen that the doctrine of bad faith has not provided protection against brands affected by the crime of dilution. So, with that, dilution regulations need to be enforced in Indonesia where its use can not only be applied to well-known brands but can also be applied to brands that can meet the requirements of the dilution doctrine.